And God knows the soldiers the authoritative and authoritarian in Islamic discourses - Abou El Fadl, Khaled 1963- (University Press of America, 2001)
This is a substantially expanded edition of the author's seminal work "The Authoritative and Authoritarian in Islamic Discourses: A Contemporary Case Study". Beginning with the case study of a Muslim basketball player who refused to stand up while the American national anthem was playing, the author documents the disintegration of the Islamic juristic tradition, and the prevalence of authoritarianism in contemporary Muslim discourses. The author analyzes the rise of what he describes as puritan and despotic trends in modern Islam, and asserts that such trends nullify the richness and diversity of the Islamic tradition. By declaring themselves the true soldiers of God and the defenders of religion, Muslim puritan movements are able to degrade women, eradicate critical thinking, and empty Islam of its moral content. In effect, the author argues, the selfdeclared protectors of Islam become its despots and oppressors who suppress the dynamism and vigor of the Islamic message. Anchoring himself in the rich Islamic jurisprudential tradition, the author argues for upholding the authoritativeness of the religious text without succumbing to authoritarian methodologies of interpretation. Ultimately, the author asserts that in order to respect the integrity of the Divine laws it is necessary to adopt rigorous analytical methodologies of interpretation, and to reinvestigate the place of morality in modern Islam